Occurrenceand characteristics of microplastics in benthic species from mangrove wetlands of Hainan, South China - Zhang, Qinzhou; Xie, Jia; Ma, Siyuan; Chen, Yingya; Lin, Fang; Diao, Xiaoping (Frontiers in Marine Science, 2023)
Microplastics (MPs) are emerging contaminants that pose a global threat to the environment. Mangrove ecosystems, which contribute to biogeochemical cycles, are vulnerable to various anthropogenic disturbances and chemical pollutants. In this study, the abundance and the characteristics of MPs were investigated in 10 species of benthic organisms, including crabs, bivalves, and snails, from seven typical mangrove distribution areas, with a total of 15 sampling sites in Hainan, South China. The abundance of MPs in each sampling site ranged between 0.83 ± 1.32 and 12.00 ± 0.00 items/individual, with an average of 3.90 ± 3.31 items/individual, while the abundance of MPs varied between 0.17 and 2.00 items/individual for the different species. Fibers (80.13%) were the most abundant MPs, most of the MPs were brown (37.18%) or blue (26.64%), and more than 80% were small-sized plastic (<2 mm). Raman analysis showed that polypropylene (94.44%) was the most dominant type of polymer. In addition, crabs (with an average abundance of 1.10 ± 0.59 items/individual) showed a higher potential for accumulating MPs than the other species investigated in the present study. This study shows that MPs are widely distributed throughout benthic species in the mangrove wetlands of Hainan.